A genus in disguise. Revision of the genus Salcedia Fairmaire, 1899 with descriptions of nine new species (Coleoptera, Carabidae, Scaritinae, Salcediini) - M Balkenohl (ZooKeys, 2020)
Specimens of the genus Salcedia Fairmaire, 1899 are rumoured to be rare. The reason for their apparent rarity might be that they are not immediately recognisable as carabids because their body surface is usually covered with a tough film and layers of mud or clay that obscure important diagnostic characters. Therefore, at first glance, these beetles look more like Colydiidae (e.g., genus Dastarcus Walker, 1858) or small Tenebrionidae (e.g., genus Gonocephalum Chevrolat, 1849). This confusion has been deepened with the traditionally short historic descriptions, leading to further misinterpretation of morphological characters on both species and suprageneric levels. The present study aims to resolve these problems by revising the species of genus Salcedia based on morphological characters after cleaning the available specimens by applying a special mild cleaning method. The revision resulted in the recognition of 18 valid species, nine of which were described as new. Because all these species seem to have been largely overlooked in the field due to their hidden way of life, all the available information concerning their biology and distribution has been summarized.